Geology, geochronology, and geochemistry of the Miocene-Pliocene Ancestral Cascades arc, northern Sierra Nevada, California and Nevada: The roles of the upper mantle, subducting slab, and the Sierra Nevada lithosphere - Cousens, B; Prytulak, J; Henry, C; Alcazar, A; Brownrigg, T (2008)
The assemblage of ca. 28-3 Ma volcanic rocks exposed in the Lake Tahoe-Reno region of the northern Sierra Nevada, United States, is interpreted to be part of the Ancestral Cascades volcanic arc. The volcanic rocks are commonly highly porphyritic, including abundant plagioclase with clinopyroxene, amphibole, and rare biotite, and range from basaltic andesite to dacite in composition. Less common are poorly phyric, olivine- and clinopyroxene-bearing basalts and basaltic andesites. Porphyritic lavas dominate composite volcanic centers, whereas the poorly phyric lavas form isolated cinder cone and lava flow complexes. Tahoe-Reno arc lavas are calc-alkaline, enriched in the large ion lithophile elements but depleted in Nb and Ta relative to the light rare earth elements, and have highly variable radiogenic isotopic compositions. Compared to the modern south Cascade arc, Tahoe-Reno region basalts are enriched in the light rare earth and large ion lithophile elements and have higher 87Sr/86Sr and lower 143Nd/144Nd that are consistent with an old, subduction-modified lithospheric mantle source, such as that proposed for lavas of the Western Great Basin. Melting of the lithospheric mantle may be enhanced by fluid flux from the subducting slab if the Juan de Fuca slab dip is shallow. Andesites and dacites evolved from basaltic magmas by a combination of fractional crystallization and assimilation of lower crustal melts. Available geochronological data indicate that the westward sweep of Cenozoic volcanism through Nevada was associated with steepening of the slab dip, but the dip angle was lower during Miocene-Pliocene arc volcanism than it is today beneath the modern south Cascades. © 2008 Geological Society of America.